Present Yourself! By MHC Class I and MHC Class II Molecules. Issue 11 (November 2016) - Rock, Kenneth L.; Reits, Eric; Neefjes, Jacques
Abstract : Since the discovery of MHC molecules, it has taken 40 years to arrive at a coherent picture of how MHC class I and MHC class II molecules really work. This is a story of the proteases and MHC-like chaperones that support the MHC class I and II molecules in presenting peptides to the immune system. We now understand that the MHC system shapes both the repertoire of presented peptides and the subsequent T cell response, with important implications ranging from transplant rejection to tumor immunotherapies. Here we present an illustrated review of the ins and outs of MHC class I and MHC class II antigen presentation. Trends: MHC molecules are critical in transplantation, autoimmunity, infections, and tumor immunotherapy. The biology of antigen presentation by MHC I and MHC II molecules provides targets for manipulation of these diseases. This biology also explains the fragments presented to the immune system and the cellular evolutionary race to escape immune control of infected and transformed cells. Many of the players determining antigen degradation and subsequent peptide loading on MHC molecules are defined and are helping to improve the accuracy of predicting presented fragments. The combined understanding of antigen presentation by MHC molecules allows exploitation to improve the responses of the cellular arm of the immune system to vaccinations and immunotherapies.